People's budget : an illustrative exercise using participatory tools - Institute for Development Policy Analysis and Advocacy (Dhaka : University Press, 2002)
With reference to Bangladesh written from the perspective of the pro-poor.
"A study commissioned by IDPAA, Proshika and conducted by Shamunnay "
Includes bibliographical references.
Keywords: Budget -- Bangladesh; Poor -- Bangladesh; Bangladesh -- Appropriations and expenditures